Partitioned pricing and consumer welfare - Kevin Ducbao Tran (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
In online commerce, obfuscation strategies by sellers are hypothesized to mislead consumers to their detriment and to the profit of sellers. One such obfuscation strategy is partitioned pricing in which the price is split into a base price and add-on fees. While empirical evidence suggests that partitioned pricing affects consumer decisions through salience effects, its consumer welfare consequences are largely unexplored. Therefore, I provide a quantification of the welfare impact of the behavioral response to partitioned pricing. To do so, I derive a discrete choice model that jointly allows for differences in the reaction to marginal changes in add-on fees and the base price as well as a discontinuous effect of a zero fee. The model is based on a framework on limited attention and I estimate it using web scraped data of posted price transactions on eBay Germany. My results suggest under-reaction to marginal changes in the shipping fee, consistent with previous results in the literature. However, I also document a discontinuous positive effect of free shipping on consumer demand, which is novel to the literature. The combined impact of these effects on consumer welfare is less than six percent of consumer surplus. The welfare impact is attenuated because the maximum shipping fee on eBay is capped and the free shipping effect partly counteracts the under-reaction to shipping fees in expectation.
Keywords: D12; D60; D83; L11; 330; partitioned pricing; limited attention; consumer welfare; shipping fees; eBay